The equality of OLS and GLS estimators in the linear regression model when the disturbances are spatially correlated - Butte Gotu (Universität Dortmund, Sonderforschungsbereich 475 - Komplexitätsreduktion in Multivariaten Datenstrukturen, 1998)
Necessary and sufficient conditions for the equality of ordinary least squares and generalized least squares estimators in the linear regression model with firstorder spatial error processes are given.
Keywords: 519; Ordinary least squares; Generalized least squares; Best linear unbiased estimator; Spatial error process; Spatial correlation